"Two Perspectives" on Teaching Crime Films. Issue 2 (3rd April 2018) - Kadleck, Colleen; Holsinger, Alexander M.
Abstract : Due to the media, many students enter undergraduate Criminal Justice programs with biased and/or entertainment-based perceptions about justice generally, and the Criminal Justice system in particular. As a result, many instructors may be compelled to do regular "myth busting" in order to instill a more realistic understanding of Criminal Justice. However, these "myths" hold potential as learning tools in a specific course that confronts and deconstructs them head on. The current paper is about the use of popular media (specifically produced films) as the primary focus of a Criminal Justice course. While such courses tend to be very popular with students, and are potentially very useful in a comprehensive curriculum, there are many considerations when implementing them effectively. Using both student and faculty perspectives, we present the major concerns that need to be considered and addressed when implementing courses that focus solely on Criminal Justice within the popular media.